2013
DOI: 10.4103/2229-5186.108802
|View full text |Cite
|
Sign up to set email alerts
|

A validated stability-indicating high performance liquid chromatographic method for moxifloxacin hydrochloride and ketorolac tromethamine eye drops and its application in pH dependent degradation kinetics

Abstract: Background and Aim:A fixed dose combination of moxifloxacin hydrochloride and ketorolac tromethamine is used in ratio of 1:1 as eye drops for the treatment of the reduction of post operative inflammatory conditions of the eye. A simple, precise, and accurate High Performance Liquid Chromatographic (HPLC) method was developed and validated for determination of moxifloxacin hydrochloride and ketorolac tromethamine in eye drops. Materials and Methods: Isocratic HPLC separation was achieved on a ACE C 18 column (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A survey of literature revealed that the KT has been analyzed in pharmaceutical preparations either alone or in combination with other drugs by HPLC (Kumaraswamy et al 2012;Razzaq et al 2012;Tsvetkova et al 2012;Dave et al 2013;Dubey et al 2012), HPTLC (Devarajan et al 2000;Vandana et al 2013), voltammetry (Squella et al 1997), and micellar electrokinetic chromatography (Orlandini et al 2004). Though these analytical procedures are sensitive, it entails a disadvantage of not being simple and requiring sophisticated experimental setup, increased cost of analysis and high consumption of solvents by the mobile phase for the chromatographic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of literature revealed that the KT has been analyzed in pharmaceutical preparations either alone or in combination with other drugs by HPLC (Kumaraswamy et al 2012;Razzaq et al 2012;Tsvetkova et al 2012;Dave et al 2013;Dubey et al 2012), HPTLC (Devarajan et al 2000;Vandana et al 2013), voltammetry (Squella et al 1997), and micellar electrokinetic chromatography (Orlandini et al 2004). Though these analytical procedures are sensitive, it entails a disadvantage of not being simple and requiring sophisticated experimental setup, increased cost of analysis and high consumption of solvents by the mobile phase for the chromatographic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…1). Various High Performance Liquid Chromatography (HPLC), High-Performance Thin-layer Chromatography (HPTLC) and spectroscopic methods are available for estimation of MOX in Active Pharmaceutical Ingredient (API) and pharmaceutical dosage form [6][7][8][9][10][11][12][13][14][15][16][17][18] . Chemically, LOT is 7-(ethyl carbonate) chloromethyl 11β,17-dihydroxy-3-oxoandrosta-1,4-diene-17β-carboxylate (fig.…”
mentioning
confidence: 99%
“…Forced degradation studies of the bulk drug sample were also performed using the following conditions: acid hydrolysis (0.1N HCl, 1N HCl), basic hydrolysis (0.1 N NaOH, 1N NaOH), heat (60-80°C for 1 hr), photolytic (UV and sunlight for up to 3 hr), oxidation (3% hydrogen peroxide for 1 hr). [21][22][23][24] Still the degradation study is needed to get a clear scenario of its degradation ways.…”
mentioning
confidence: 99%